Transformation of Mahārah al-Kalām Learning Based on Artificial Intelligence (AI) at MA Assunniyyah Al Jauhari Kencong Jember - Nor Holis Bin Nafsah; Immatul Khoiroh; M. Abdul Ghofur; Ahmad Mizan Rosyadi Abdul Jalil Mannan; Ubaidillah Ali Al Karim (Al-Fusha : Arabic Language Education Journal, 2026)
Arabic is often perceived as difficult by students, resulting in low learning interest. Therefore, instructional innovation is needed through the use of Artificial Intelligence (AI)-based media that creates interactive, engaging, and adaptive learning environments. This study aims to describe the planning, implementation, and evaluation of AI media in improving students’ mahārah al-kalām at Madrasah Aliyah As-Sunniyyah Al-Jauhari Kencong Jember. This research employs a descriptive qualitative method with data collected through observation, interviews, and documentation. The AI media used include speech recognition applications and interactive chatbots that support speaking, listening, and reading skills. The findings show that planning involves lesson plan development, media selection, and the implementation of the Merdeka Curriculum. The implementation is carried out through conversational methods and speaking exercises. Evaluation results indicate improvements in students’ participation, confidence, and willingness to speak Arabic.